IMPLEMENTASI WEB SCRAPING DALAM PENGUMPULAN BERITA KRIMINAL PADA MASA PANDEMI COVID-19 - Salim Satriajati; Satria Bagus Panuntun; Setia Pramana (Seminar Nasional Official Statistics, 2020)
Currently, there are many news sites that provide information related to events and phenomena. On the other hand, the Covid-19 pandemic gave rise to multidimensional crises and problems. One of them is the emergence of crime in the community. This study aims to collect news on crimes that occurred during the Covid-19 pandemic from news sites. The collection of information from news sites uses web scraping techniques. Web scraping is a technique of extracting information from websites. Then, the news that has been collected can be analyzed regarding the possible trend of criminal incidents along with the trend of the Covid-19 pandemic in Indonesia. The news site used in this study is detik.com. Based on the Alexa Internet site (alexa.com), detik.com is one of the most frequently accessed news sites and included in the top 10 websites with the highest traffic in Indonesia. Meanwhile, data of Covid-19 in Indonesia comes from the KawalCOVID19.id website. The results showed that the number of criminal news reports and the number of confirmed cases of Covid-19 had the same daily trend, which was increasing. Based on this research, it can be concluded that web scraping can be implemented to gather news. The results of web scraping can then be used to find out the trend of the number of daily criminal news which is then compared with the daily trend of the number of confirmed cases of Covid-19 in Indonesia.